RADICALIZATION IN THE TEACHING RELIGION AND ITS RELATIONS WITH CRIMINAL ACTS OF TERRORISM - Hasibuan, Hoiruddin; Sudarsono, Sudarsono; Nurjaya, I Nyoman; Sugiri, Bambang (Brawijaya Law Journal, 2017)
The criminal act of terrorism is a crime against humanity, human civilization and constitute a serious threat to the integrity and sovereignty of a nation. In fact, terrorism can be a threat to a state security and sovereignty as well as world peace.It is argued that one of the main causes of criminal acts of terrorism is radicalization. Thus, this paper seeks to analyze the casual link between radicalization and terrorism. This paper determines to what extent does the radicalization affected the criminal acts of terrorism. This research uses a juridical normative method by analyzing legal instruments relating to terrorism and seeks to analyze the reason behind the provided rules.This paper submitted that while radicalization affected terrorism, de-radicalization is urgent in responding to terrorism. This paper also proposes how de-radicalization works in preventing terrorism.